ANALISIS VALIDITAS REFERENSI DAN KETEPATAN SITASI PADA MAKALAH ILMIAH MAHASISWA SEMESTER II PENDIDIKAN BAHASA INDONESIA - Hoirina Pulungan; Regita Amelia; Shiwi Sulistyani; Tia Maharani; Achmad Yuhdi (Indonesian language and literature education program Majapahit Islamic University, 2026)
This study aims to analyze the validity of references and the accuracy of citations in scientific papers written by second-semester students in the Indonesian Language and Literature Education Program. The research focuses on the use of reference sources, the consistency between in-text citations and the reference list, and the accuracy of citation formatting. The study employs a descriptive qualitative approach using a document analysis method on five student papers selected through purposive sampling. Data were collected via documentation techniques and analyzed using content analysis to identify patterns in reference usage and citation errors. The results indicate that the sources used are still dominated by textbooks and general internet sources, while the use of scientific journals remains limited. Additionally, inconsistencies were found between in-text citations and the reference list, as well as inconsistencies in citation formatting. These findings indicate that students’ academic literacy skills still need to be improved through more systematic instruction and training in scientific writing. Keywords: scientific references, citations, academic literacy, student scientific writing.